Diagnostic performance of six ultrasound-based risk stratification systems in thyroid follicular neoplasm: A retrospective multi-center study - Yang, Jingjing; Sun, Yu; Li, Xingjia; Zhao, Yueting; Han, Xue; Chen, Guofang; Ding, Wenbo; Li, Ruiping; Wang, Jianhua; Xiao, Fangsen; Liu, Chao; Xu, Shuhang (Frontiers in Oncology, 2022)
This study aimed to compare the diagnostic performances of six commonly used ultrasound-based risk stratification systems for distinguishing follicular thyroid adenoma (FTA) from follicular thyroid carcinoma (FTC), including the American Thyroid Association Sonographic Pattern System (ATASPS), ultrasound classification systems proposed by American Association of Clinical Endocrinologists, American College of Endocrinology, and Associazione Medici Endocrinology (AACE/ACE/AME), Korean thyroid imaging reporting and data system (K-TIRADS), European Thyroid Association for the imaging reporting and data system (EU-TIRADS), American College of Radiology for the imaging reporting and data system (ACR-TIRADS), and 2020 Chinese Guidelines for Ultrasound Malignancy Risk Stratification of Thyroid Nodules (C-TIRADS). A total of 225 FTA or FTC patients were retrospectively analyzed, involving 251 thyroid nodules diagnosed by postoperative pathological examinations in three centers from January 2013 to October 2021. The diagnostic performances of six ultrasound-based risk stratification systems for distinguishing FTA from FTC were assessed by plotting the receiver operating characteristic (ROC) curves and compared at different cut-off values. A total of 205 (81.67%) cases of FTA and 46 (18.33%) cases of FTC were involved in the present study. Compared with those of FTA, FTC presented more typical ultrasound features of solid component, hypoechoic, irregular margin and sonographic halo (all P<0.001). There were no significant differences in ultrasound features of calcification, shape and comet-tail artifacts between cases of FTA and FTC. There was a significant difference in the category of thyroid nodules assessed by the six ultrasound-based risk stratification systems (P<0.001). The areas under the curve (AUCs) of ATASPS, AACE/ACE/AME, K-TIRADS, EU-TIRADS, ACR-TIRADS and C-TIRADS in distinguishing FTA from FTC were 0.645, 0.729, 0.766, 0.635, 0.783 and 0.798, respectively. Our study demonstrated that all the six ultrasound-based risk stratification systems present potential in the differential diagnosis of FTA and FTC. Specifically, C-TIRADS exerts the best diagnostic performance among the Chinese patients. ATASPS possesses a high sensitivity, while K-TIRADS possesses a high specificity in distinguishing FTA from FTC.